Analysis of Energy Dissipation Channels in a Benchmark System of Activated Dissociation: N(2) on Ru(0001) - Shakouri, Khosrow (J Phys Chem C Nanomater Interfaces, 2018)
[Image: see text] The excitation of electron–hole pairs in reactive scattering of molecules at metal surfaces often affects the physical and dynamical observables of interest, including the reaction probability. Here, we study the influence of electron–hole pair excitation on the dissociative chemisorption of N(2) on Ru(0001) using the local density friction approximation method. The effect of surface atom motion has also been taken into account by a high-dimensional neural network potential. Our nonadiabatic molecular dynamics simulations with electronic friction show that the reaction of N(2) is more strongly affected by the energy transfer to surface phonons than by the energy loss to electron–hole pairs. The discrepancy between the computed reaction probabilities and experimental results is within the experimental error both with and without friction; however, the incorporation of electron–hole pairs yields somewhat better agreement with experiments, especially at high collision energies. We also calculate the vibrational efficacy for the N(2) + Ru(0001) reaction and demonstrate that the N(2) reaction is more enhanced by exciting the molecular vibrations than by adding an equivalent amount of energy into translation.